2013
DOI: 10.1371/journal.ppat.1003491
|View full text |Cite|
|
Sign up to set email alerts
|

Irf8-Regulated Genomic Responses Drive Pathological Inflammation during Cerebral Malaria

Abstract: Interferon Regulatory Factor 8 (IRF8) is required for development, maturation and expression of anti-microbial defenses of myeloid cells. BXH2 mice harbor a severely hypomorphic allele at Irf8 (Irf8R294C) that causes susceptibility to infection with intracellular pathogens including Mycobacterium tuberculosis. We report that BXH2 are completely resistant to the development of cerebral malaria (ECM) following Plasmodium berghei ANKA infection. Comparative transcriptional profiling of brain RNA as well as chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 72 publications
2
61
0
Order By: Relevance
“…The analysis of the IRF8 and IRF1 cistromes confirmed a major role of these IRF family members in macrophage function, including response of these cells to infectious and inflammatory stimuli (Kubosaki et al, 2010;Berghout et al, 2013;Mancino et al, 2015). The loss of IRF8 binding leads to defective expression of genes critical for antigen presentation pathway and instructive molecules for T cell activation, but also response to stimuli such as cytokine receptors, pathogen-associated molecular pattern receptors, comple- p-values were calculated using Student's t test).…”
Section: Discussionmentioning
confidence: 80%
“…The analysis of the IRF8 and IRF1 cistromes confirmed a major role of these IRF family members in macrophage function, including response of these cells to infectious and inflammatory stimuli (Kubosaki et al, 2010;Berghout et al, 2013;Mancino et al, 2015). The loss of IRF8 binding leads to defective expression of genes critical for antigen presentation pathway and instructive molecules for T cell activation, but also response to stimuli such as cytokine receptors, pathogen-associated molecular pattern receptors, comple- p-values were calculated using Student's t test).…”
Section: Discussionmentioning
confidence: 80%
“…Surprisingly, this analysis also clearly showed that despite being in the normal range (Figures 1 and 3B), the patient's T cells are in a more naïve state, with a striking depletion of Th1 activated CD4 1 T cell, and of CD4 1 and of CD8 1 antigen-experienced memory T-cell gene signatures ( Figure 2C). This suggests that the primary defect of APCs in K108E is associated with a secondary defect in lymphoid cells.We also compared the list of transcripts altered in the K108E patient (supplemental Table 1) with a list of direct transcriptional targets of IRF8 that we identified by sequencing of IRF8-specific chromatin (ChIP-seq) immunoprecipitated from a macrophage cell line treated with IFN-g. 24 We noted a strong and significant depletion of transcripts from genes close to IRF8 binding sites in the K108E patient (Figures 2A and 3F). Such genes represent major and direct IRF8 transcriptional targets in vivo in myeloid cells, expression of which is abrogated in the patient.…”
mentioning
confidence: 80%
“…Proinflammatory Th1 cytokines produced by T cells are required for protection against intracellular infections (15). We evaluated the response of Themis I23N mice to infection with M. tuberculosis.…”
Section: Resultsmentioning
confidence: 99%
“…Antibody-mediated cell ablation experiments have demonstrated a strong pathological role for CD8 ϩ and CD4 ϩ T cells, NK cells, and neutrophils in ECM (7). Conversely, we and others have demonstrated an ECM-protective effect of mutations in major proinflammatory genes such as those for IFN-␥ (Ifng) and its receptor (Ifngr1), lymphotoxin (Lta/Ltb), complement component 5a (Hc) (reviewed in reference 13), and certain transcription factors that regulate the expression of these genes in myeloid and lymphoid cells, including IFN regulatory factor 1 (IRF1) (14), IRF8, and STAT1 (15). Whole-brain transcript profiling along with chromatin immunoprecipitation and sequencing data comparing ECM-susceptible and -resistant (Irf8 myls BXH2 strain) mice identified a core transcriptome activated during ECM (15).…”
Section: Damping Of Proinflammatory Responses In Themismentioning
confidence: 99%
See 1 more Smart Citation